Overexpression of OsCM alleviates BLB stress via phytohormonal accumulation and transcriptional modulation of defense-related genes in Oryza sativa - Jan, Rahmatullah (Sci Rep, 2020)
Xanthomonas oryzae is a serious pathogen causing bacterial leaf blight (BLB) disease in rice, markedly reducing its yield. In this study, the rice chorismate mutase (OsCM) gene was overexpressed in a bacterial leaf blight-susceptible rice line to investigate the functional role of OsCM in response to bacterial leaf blight stress. We reported that overexpression of OsCM altered the downstream pathway of aromatic amino acids, mitigating pathogen stress by altering stress-responsive genes and hormonal accumulation. Phenotypic evaluation showed that the lesion length in the transgenic line was significantly lesser than that in the wild-type, suggesting greater resistance in the transgenic line. Further analysis revealed that OsCM expression induced phenylalanine accumulation and suppressed tyrosine accumulation in response to bacterial leaf blight stress. Furthermore, bacterial leaf blight stress induced genes downstream of the phenylpropanoid pathway in conjunction with OsCM, suggesting that the phenylpropanoid pathway is dependent on OsCM gene expression. We reported high SA and low JA accumulation in response to bacterial leaf blight stress in the transgenic line. This higher SA accumulation suggested that SA induces immune responses by functioning as a promoter of nonexpresser pathogenesis-related genes 1 (NPR1) transcriptional regulation. Xa7 expression was induced with increase in nonexpresser pathogenesis-related genes 1, which is thought to be responsible for Xa7 expression, which is responsible for mitigating bacterial leaf blight stress.